Academic Supervision of School Principals, Principal Transformational Leadership, and School Climate on Senior High School Teachers' Competence - Longginus Laga Belan; M.D Niron (AL-ISHLAH: Jurnal Pendidikan, 2021)
The study aims to determine and describe the effect of principal academic supervision, principal transformational leadership, and school climate toward pedagogic and professional competence of teachers in Senior High School in Lembata Regency. The research uses a quantitative approach with the ex-post facto type. The population was 200 teachers of Senior High School who taught national exam subjects in Lembata Regency. The sample was 127 teachers using the simple random sampling technique. Data collection used is questionnaires with expert validation and empirical tests. Multiple regressions are used to analyze the data. Based on the study results, it was found that the principal's academic supervision affected teacher competence. The principal's transformational leadership also affected teacher competence, and the school climate affected teacher competence. So that the principal's academic supervision, principal's transformational leadership, and school climate on teacher competence in Lembata.